Sources and fates of NO3− and PO43− in an alluvial plain wetland - Insights from the Auzon oxbow and the alluvial aquifer of the Allier (Auvergne, France) - Aumar, Cyril; Celle, Hélène; Quenet, Mélanie; Voldoire, Olivier; Allain, Elisabeth; Garreau, Alexandre; Caillon, Nicolas; Nevers, Pierre; Devidal, Jean-Luc; Mailhot, Gilles; Beauger, Aude (Applied geochemistry, 2025)
The continental hydrosystems of wetlands play fundamental socio-economic and environmental roles in all aquatic environments. These ecosystems, when located at the interface between surface and groundwater, such as oxbows, are of crucial importance in regulating water and nutrient flows. They help control water quality and provide ideal habitats for often fragile species. The transfer of contaminants into the different compartments of the groundwater-wetland-river continuum is difficult to characterize because they are most often of different types and origins within the same hydrosystem. The objective of this study is to characterize water quality and water exchange using a multi-tracer approach combining monthly hydrochemical monitoring, isotopic characterization of NO3− molecules (δ18ONO3 and δ15NNO3) and concentration of chemical micropollutant particles. This methodology is applied to a fluvial annex of the Allier River, the Auzon oxbow hydrosystem, subject to moderate environmental and anthropogenic pressure (low level of industrialization and urbanization, mixed conventional farming). Nitrate (NO3−) and phosphate (PO43−) concentrations do not behave in the same way over time: NO3− has a seasonal dynamic, whereas phosphates are disconnected from the hydrological regime. Some subsystems of the Auzon oxbow are undergoing denitrification, demonstrating the importance of preserving these environments for their nutrient regulation potential. As for chemical micropollutants and PO43−, the low overall concentration of these two contaminants, coupled with the high dilution potential of the Auzon oxbow hydrosystem, means that average concentrations remain within acceptable standards for surface waters. Based on these results, the Auzon hydrosystem is maintaining good ecological quality despite nutrient flows from multiple sources. The multi-tracer approach used in this study demonstrates its effectiveness in determining the origin of nutrients, and it could be applied to other studies in contexts where environmental and societal pressures are significantly higher. •Nitrates derive from agricultural practice while phosphates result from human activities.•Dynamic of NO3− is seasonal in surface water, and more sporadic for PO43-.•Denitrification processes take place in alluvial aquifers and in riparian wetlands.